Modeling Based on Semi-tensor Product for Radiant Floor Cooling Systems. (2017) - Qin, Fenghua; Wang, Chongjie; Feng, Liye; Lv, Hongli
Abstract: There are many factor which have impact on the performance of radiant floor systems. There it is very hard to build an accurate math model to describe the system which is applied to practice. The model based on semi-tensor product (STP) and fuzzy control is employed to analyse the dynamic performance of radiant floor systems. In this paper, a radiant floor cooling system based on concrete core radiant floors is examined. To analyse dynamic behaviour of radiant floor system, the model is used to estimate quantitatively related parameters in the start-up period of the floor systems under the impact of outdoor environment such as temperature and humidity. The results show that it is not evident to time delay of the floor surface temperature and indoor air temperature due to the thermal inertia while the amplitude of outdoor air temperature vibration is reduced significantly.